KATA MAJEMUK BAHASA BAKUMPAI DI KABUPATEN BARITO KUALA (BAKUMPAI LANGUAGE COMPOUND WORDS IN BARITO KUALA REGENCY) - Ida Royani (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2021)
Abstract Bakumpai Language Compound Words in Barito Kuala Regency. This study aims to describe and explain the features, forms, and meanings of compound words in the Bakumpai language in Barito Kuala Regency, South Kalimantan Province. The study of the characteristics, form and meaning of the Bakumpai compound words is based on several theories and research that have been done before. This linguistic research uses descriptive qualitative methods with interview, recording, documentation, and introspection techniques. The qualitative data presented in the spoken form is a number of compound words in the form of Bakumpai compound words. Research on the Bakumpai compound words obtained empirical data related to the characteristics, form, and meaning of the Bakumpai compound words in Barito Kuala Regency. Compound words in the Bakumpai language have morphological and syntactic characteristics that can be seen from the number of word components, compound words with inseparable components, compound words with noninterchangeable word components, compound words with repetitive form word components, compound words with word components affixed forms, compound words with bound word components, and compound words with certain word components. Bakumpai compound words have recognizable forms based on the form of word components in the form of free and bound forms, components based on certain categories or types of words, exocentric and endocentric compound word construction, and the function of word components in syntactic valence as S, P O, and Description. The meaning of compound words in the Bakumpai language can be divided into compound words which have grammatical, idiomatic meaning, the meaning of synonymous words, and the meaning seen from certain word components. Key words: compound words, Bakumpai language, morphological Abstrak Kata Majemuk Bahasa Bakumpai di Kabupaten Barito Kuala. Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan tentang ciri, bentuk, dan makna kata majemuk bahasa Bakumpai di Kabupaten Barito Kuala Provinsi Kalimantan Selatan. Kajian mengenai ciri, bentuk, dan makna kata majemuk bahasa Bakumpai didasarkan pada beberapa teori dan penelitian yang pernah dilakukan sebelumnya. Penelitian kebahasaan ini menggunakan metode deskriptif kualitatif dengan teknik wawancara, perekaman, dokumentasi, dan instropeksi. Data kualitatif yang disajikan dalam bentuk lisan adalah sejumlah gabungan kata yang berupa kata majemuk bahasa Bakumpai. Penelitian mengenai kata majemuk bahasa Bakumpai memperoleh data empiris yang berkaitan dengan ciri, bentuk, dan makna kata majemuk bahasa Bakumpai di Kabupaten Barito Kuala. Kata majemuk bahasa Bakumpai memiliki ciri morfologis dan ciri sintaksis yang dapat dilihat dari jumlah komponen kata, kata majemuk dengan komponen yang tidak dapat dipisahkan, kata majemuk dengan komponen kata yang tidak dapat dipertukarkan, kata majemuk dengan komponen kata bentuk perulangan, kata majemuk dengan komponen kata bentuk berimbuhan, kata majemuk dengan komponen kata bentuk terikat, dan kata majemuk dengan komponen kata tertentu. Kata majemuk bahasa Bakumpai memiliki bentuk yang dapat dikenali berdasarkan bentuk komponen kata yang berupa bentuk bebas dan terikat, komponennya yang didasarkan pada kategori atau jenis kata tertentu, konstruksi kata majemuk yang eksosentris dan endosentris, dan fungsi komponen kata dalam valensi sintaksis sebagai S,P,O, dan Keterangan. Makna kata majemuk bahasa Bakumpai dapat dibedakan menjadi kata majemuk bermakna gramatikal, idiomatikal, makna kata bersinonim, dan makna dilihat dari komponen kata tertentu. Kata-kata kunci: kata majemuk, bahasa Bakumpai, morfologis